Advanced glycation end products regulate the receptor of AGEs epigenetically - Wu, Xiaoqing; Shi, Xuanren; Chen, Xiaoyong; Yin, Zhanhai (Frontiers in Cell and Developmental Biology, 2023)
AGEs can boost its receptor RAGE expression through the downstream signaling pathway to facilitate AGE-RAGE interaction. In this regulation process, the primary signaling pathway is NF-κB and STAT3 pathway. However, the inhibition of these transcription factors can not completely block the upregulation of RAGE, which indicates AGEs may also impact RAGE expression via other pathways. In this study, we revealed that AGEs can exert epigenetic impacts on RAGE expression. Here, we utilized carboxymethyl-lysine (CML) and carboxyethyl-lysine (CEL) to treat liver cells, and discovered that AGEs can promote the demethylation of RAGE promoter region. To verified this epigenetic modification, we employed dCAS9-DNMT3a with sgRNA to specifically modify the RAGE promoter region against the effect of CML and CEL. The elevated RAGE expression were partially repressed after AGE-induced hypomethylation status were reversed. Additionally, TET1 were also upregulated in AGE-treated cells, indicating AGEs may epigenetically modulate RAGE through elevating TET1 level.